2015
DOI: 10.1159/000430189
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Mutation in the SCN5A Gene Associated with Brugada Syndrome

Abstract: Background: Brugada syndrome (BrS) is a genetically determined cardiac electrical disorder, characterized by typical electrocardiography (ECG) alterations, and it is an arrhythmogenic syndrome that may lead to sudden cardiac death. The most common genotype found among BrS patients is caused by mutations in the SCN5A gene, which lead to a loss of function of the cardiac sodium (Na+) channel (Nav1.5) by different mechanisms. Methods: The assay of confocal laser microscopy and western blot w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…13 Dimerization affects severity of pain-linked mutation induced hNav1.7 gating changes 14 Inhibiting dimerization drastically reduced the persistent current of hNav1.7/A1632E ( Fig. 5 shown that the co-expression of a trafficking deficient mutation with WT reduced channel expression 27 on the cell membrane (Wang et al, 2015). There might be parallels between these findings and those 28 reported here on the hNav1.7/R896Q mutation.…”
Section: (Supplementarysupporting
confidence: 51%
“…13 Dimerization affects severity of pain-linked mutation induced hNav1.7 gating changes 14 Inhibiting dimerization drastically reduced the persistent current of hNav1.7/A1632E ( Fig. 5 shown that the co-expression of a trafficking deficient mutation with WT reduced channel expression 27 on the cell membrane (Wang et al, 2015). There might be parallels between these findings and those 28 reported here on the hNav1.7/R896Q mutation.…”
Section: (Supplementarysupporting
confidence: 51%
“…Perhaps, the most complete hNa v 1.5 model developed so far was the model reported by Wang et al 14 This model focused on a rare L812Q mutation located at the S4 helix of domain II. The models for the individual four transmembrane sub-domains were generated through the PHYRE2 15 server and assembled through a superposition on the NavAB bacterial ion channel using Chimera software.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in the Chinese population, localized in the domain II S4 segment of NaV1.5 α subunit protein, a new mutation, L812Q mutation, has been described. In this study, it was shown that this mutation improved the sodium channel inactivation process and disrupted the membrane expression of the canal in BrS patients [18]. In a Dutch population study, it was determined that SCN5A gene mutations, which cause loss of function in BrS patients, are associated with dilation and deterioration in contractile function of both ventricles [20].…”
Section: Scn10a Gene Polymorphismmentioning
confidence: 93%
“…Depolarization or repolarization of cardiac action potential may be affected by due to reduced sodium current. Nevertheless, the underlying pathophysiological mechanism of the BrS phenotype is still being discussed [18]. BrS is defined as a disease characterized by sudden cardiac death characterized by a right bundle branch with an ST segment elevation in leads V1 and V2 in 1992.…”
Section: Scn10a Gene Polymorphismmentioning
confidence: 99%